Effectiveness of Innovative TikTok-Based Educational Multimedia for Nutrition Education Among Adolescent Girls - Baiq Fitria Rahmiati; Ali Khomsan; Hadi Riyadi; Cesilia Meti Dwiriani (Universitas Bumigora, 2026)
Adolescent girls are vulnerable to nutritional problems due to the increasing nutritional requirements during growth and development, while inadequate nutrition knowledge may contribute to unhealthy dietary behaviors. Innovative and engaging educational approaches are needed to improve nutrition knowledge among adolescents. This study aimed to evaluate the effectiveness of innovative TikTok-based educational multimedia for nutrition education among adolescent girls. The method of this research was a quasi-experimental study with a pretest–posttest control group design conducted from July to November 2025 involving 60 adolescent girls from two junior high schools in West Nusa Tenggara, Indonesia. Participants were selected using systematic random sampling and assigned to either an intervention group (n=30) or a control group (n=30). The intervention group received nutrition education through innovative TikTok-based educational multimedia consisting of short educational videos, while the control group received conventional nutrition education. Nutrition knowledge was assessed before and after the 16-week intervention using a validated questionnaire. Data were analyzed using descriptive and inferential statistics with a significance level of p<0.05. The results showed a significant improve ment in nutrition knowledge among participants in the intervention group (p<0.001), whereas no significant change was observed in the control group (p=0.678). Furthermore, a significant difference in post-intervention knowledge scores was found between the intervention and control groups (p=0.001). These findings indicate that TikTok-based educational multimedia is an effective and accessible tool for improving nutrition knowledge among adolescent girls and may serve as an innovative strategy for school-based nutrition education programs.